The Relationship between fiscal policy and household consumption (case of Algeria for the period 1985–2021) - magoura, khaled; benazza, mohammed (Journal of Research in Finance and Accounting, 2023)
This study aims to discover the impact of the fiscal policy on household consumption in Algeria for the period 1985–2021 by using non-linear regression models (NARDL). The findings denote the existence of a positive and significant relationship between the positive shocks of direct taxes and household consumption on one side and a negative and significant relationship between the positive shocks of government expenditures and household consumption on the other side in the short term. In the long run, the study found a positive and significant relationship between the positive shocks of direct taxes and household consumption, but not one between the government and household consumption